Impact of multi-scenario land-use changes on habitat quality evolution in the Yangtze River economic belt - Dong, Bowen; Huang, Tiantian; Tang, Tao; Huang, Delin; Tang, Chen (Frontiers in Environmental Science, 2025)
Ecosystems worldwide are facing significant challenges resulting from the dual pressures of global climate change and human activities, particularly in terms of significant biodiversity loss associated with land-use change. Focusing on the Yangtze River Economic Belt (YREB), this study uses the System Dynamics (SD) - Patch-generating Land Use Simulation (PLUS) model to simulate land-use development under different scenarios of shared socio-economic pathways (SSPs) and representative concentration pathways (RCPs) from 2030 to 2050. Furthermore, the InVEST model is applied to evaluate changes in habitat quality (HQ) over the period 2000 to 2050. A hotspot analysis further highlights the spatial heterogeneity of HQ within the YREB. The study showed that the land-use pattern in the YREB from 2020 to 2050 will be dominated by cropland in the eastern region, grassland in the north-west, and forest land in the central and southern regions, with a steady increase in built-up land in the east. The HQ index exhibits a gradual increase from east to west, ultimately declining to 0.726 under the SSP585 scenario for 2050. This trend reflects moderate habitat degradation (HD), with the degree of degradation shifting towards lower and higher proportions of HQ. Spatial analysis of HQ further reveals that the eastern region is identified as a cold spot, the central region is categorized as non-significant, while the western region emerges as a hot spot, where HQ exceeds 40%. These findings offer a scientific foundation for promoting high-quality development and enhancing biodiversity conservation in the YREB.